Protocolo de prevenção e tratamento da lesão por fricção - Saito, Celina Mayumi Morita [UNIFESP] (2017)
Introduction: Skin tear is a traumatic wound caused by friction alone or in combination with shearing, leading to partial or total separation of the dermis from the epidermis. It mainly affects people in the extremes of age, such as neonates and the elderly. Health professionals should have knowledge of skin tears for proper prevention and treatment. Objective: To develop and implement a protocol for the prevention and treatment of skin tears at the Hospital São Paulo (HSP). Methods: This is a cross-sectional study on the development of a protocol for the prevention and treatment of skin tears to be implemented at the HSP. For the development of the protocol content, a literature search was conducted in the MEDLINE and SciELO databases in the period from September 2016 to November 2016 . Protocol validation was performed with specialists in wound prevention and treatment, using the Delphi technique. Face-to-face training was provided to nursing professionals and a module was developed for the hospital's online continuing education program. Results: The protocol and a poster were made available both in print and online format. The developed protocol was implemented at the HSP and 636 health professionals participated in the training. The protocol was made available online and in print in the hospital units. A poster with a simplified version of the protocol was placed on bulletin boards of hospital units. An educational module was then incorporated into the online continuing education program for nursing professionals of the HSP. Conclusion: The protocol for the prevention and treatment of skin tears was developed and implemented at the HSP.